Urgensi Pendidikan Hukum Digital bagi Generasi Muda dalam Mewujudkan Keadaulatan Siber Nasional - Nur Aripkah; Khairunnisa Noor Asufie (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Technological advances have an impact on social change, a shift that was originally done conventionally in the real world but can now be done digitally in cyberspace. The use of the internet is supported by gadgets and applications that make it easier for people in their daily activities to make the statement